THE CONTRIBUTION OF LAND AND BUILDING TAX IN OPTIMISING LOCAL TAX REVENUE (Case Study at BAPENDA Subang in 2016-2020) - Silvia Marcelina; Indah Umiyati (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2021)
The existence of local tax contributions can optimize regional revenues, especially contributions from earth and building taxes that have always been the prima donna of local taxes. The purpose of this study is to find out the extent of the target and realization of earth and building tax revenues in Subang Regency during 2016-2020, to find out the contribution of earth and building taxes to local tax revenues in Subang Regency during 2016-2020, and to know the strategies and controls carried out by BAPENDA in optimizing subang district tax revenues. This research is conducted in two ways, namely first, processing secondary data using contribution formulas and then interpreted at the level of contribution value, secondly confirming the results of the calculation of the data and identifying the causes of the increase or decrease in un acceptance and contribution and identifying bapenda strategy and control by doing wawanacara virtually with KABID PBB and BPHTB BAPENDA Subang based on operationalization of a predefined prameter. The results of this study show first, the average target trend and realization of PBB admissions for 5 years is 103.66% if interpreted then un acceptance is included in the criteria